Predictors of Post-Traumatic Stress Symptoms after musculoskeletal trauma - Ferozkhan Jadhakhan; Deborah Falla; Alexander Dallaway (PLoS ONE, 2026)
Background Post-traumatic stress symptoms (PTSS) are common following musculoskeletal trauma and are associated with poorer recovery, disability, and reduced quality of life. Although psychosocial and injury-related factors have been linked to PTSS, limited research has examined longitudinal predictors or the relationship between injury severity and PTSS progression in people hospitalised for musculoskeletal trauma. Objectives To identify predictors of PTSS at three and six months following musculoskeletal trauma and hospitalisation, and to examine the relationship between injury severity and PTSS severity over time. Methods This secondary analysis of a prospective cohort study included 125 adults admitted to a UK major trauma centre with acute musculoskeletal injuries. PTSS were assessed using the Impact of Event Scale–Revised (IES-R) at baseline, three, and six months, with scores ≥22 indicating elevated PTSS. Candidate predictors included socio-demographic, clinical, and trauma-related variables. Multivariate logistic regression identified predictors at three and six months. Multicollinearity was assessed using variance inflation factors and principal component analysis. Injury severity (mild, moderate, major) was examined using Kruskal-Wallis and Mann-Whitney U tests. Model discrimination and calibration were evaluated using AUC and Hosmer-Lemeshow tests. Results At baseline, 97.6% of participants met the PTSS threshold, decreasing to 26.4% at three months and 17.6% at six months. This high baseline prevalence likely reflects the early post-injury assessment period and the use of a sensitive screening threshold. At three months, road traffic accidents (OR 3.71, 95% CI 2.60–6.85) and car accidents (OR 2.20, 95% CI 1.68–3.15) significantly increased PTSS risk compared to falls. Higher baseline anxiety (OR 0.53, 95% CI 0.33–0.86) and kinesiophobia (OR 0.58, 95% CI 0.39–0.86) were associated with reduced PTSS odds. At six months, higher chronic pain–related disability independently predicted lower PTSS risk (OR 0.89, 95% CI 0.82–0.97). Injury severity differed significantly at six months (p = 0.022) but not at three months (p = 0.172). The six-month model demonstrated excellent discrimination (AUC = 0.91) and good calibration (p = 0.70). Conclusions PTSS following musculoskeletal trauma are influenced by trauma mechanism, psychological factors, and injury severity over time, supporting early risk stratification and targeted psychological intervention.